Enhancing human capillary tube network assembly and maturation through upregulated expression of pericyte-derived TIMP-3 - Yrigoin, Ksenia; Bernard, Kaitlyn N.; Castaño, Maria A.; Cleaver, Ondine; Sumanas, Saulius; Davis, George E. (Frontiers in Cell and Developmental Biology, 2024)
In this study, we identify and characterize new molecular determinants that optimize human capillary tube network assembly. Our lab has previously reported a novel, serum free-defined 3D co-culture model using human endothelial cells (ECs) and human pericytes whereby EC-lined tubes form and co-assemble with pericytes, but when these cultures are maintained at or beyond 5 days, tubes become progressively wider and unstable. To address this issue, we generated novel human pericytes that carry a tissue inhibitor of metalloproteinase (TIMP)-3 transgene which can be upregulated following doxycycline addition. EC-pericyte co-cultures established in the presence of doxycycline demonstrated marked enhancement of capillary network assembly including dramatic narrowing of capillary tube widths to an average of 8 µm (physiologic capillary tube width), increased tube lengths, increased tube branching, and robust stimulation of basement membrane matrix assembly, particularly with collagen type IV and fibronectin deposition compared to controls. These substantial changes depend not only on induction of pericyte TIMP-3, but also on recruitment of pericytes to EC tubes. Blockade of pericyte recruitment prevents these dramatic capillary network alterations suggesting that EC-pericyte interactions and induction of pericyte TIMP-3 are necessary together to coordinate and facilitate capillary assembly and maturation. Overall, this work is critical for our basic understanding of capillary formation, but also for the ability to reproducibly generate stabilized networks of capillary tubes.